2022
DOI: 10.3390/biomedicines10020209
|View full text |Cite
|
Sign up to set email alerts
|

The Cytogenetic Profile of Primary and Secondary Plasma Cell Leukemia: Etiopathogenetic Perspectives, Prognostic Impact and Clinical Relevance to Newly Diagnosed Multiple Myeloma with Differential Circulating Clonal Plasma Cells

Abstract: Plasma cell leukemia (PCL) is a rare and aggressive plasma cell dyscrasia that may appear as de-novo leukemia (pPCL) or on the basis of a pre-existing multiple myeloma (MM), called secondary plasma cell leukemia (sPCL). In this prospective study, we have applied a broad panel of FISH probes in 965 newly diagnosed MM (NDMM) and 44 PCL cases of both types to reveal the particular cytogenetic differences among the three plasma cell dyscrasias. In order to evaluate the frequency and patterns of clonal evolution, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…However, none of them are speci c to PCL. Immunoglobulin heavy chain (IgH) translocations including t(4;14), t(11;14) and t(14;16), 8q24 rearrangements, TP53 inactivation, K-RAS and N-RAS mutations, deletion of chromosome 17, deletion of chromosome 13, 1p loss or lq gains and monosomy 13 have been de ned in PCL [1,11,12]. The t(14;20) is seen less frequently in PCL [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, none of them are speci c to PCL. Immunoglobulin heavy chain (IgH) translocations including t(4;14), t(11;14) and t(14;16), 8q24 rearrangements, TP53 inactivation, K-RAS and N-RAS mutations, deletion of chromosome 17, deletion of chromosome 13, 1p loss or lq gains and monosomy 13 have been de ned in PCL [1,11,12]. The t(14;20) is seen less frequently in PCL [13].…”
Section: Discussionmentioning
confidence: 99%
“…pPCL is frequently associated with t(11;14) and sPCL with t(4;14). 72 Translocation t(11;14) a standard risk marker in MM is associated with an aggressive course in patients of pPCL. [72][73][74] The two genes reported to be involved in t (11;14) are CCND1 and MYEOV.…”
Section: Role Of Fish In Other Plasma Cell Dyscrasiasmentioning
confidence: 99%
“…72 Translocation t(11;14) a standard risk marker in MM is associated with an aggressive course in patients of pPCL. [72][73][74] The two genes reported to be involved in t (11;14) are CCND1 and MYEOV. MYEOV is not commonly seen involved in MM patients.…”
Section: Role Of Fish In Other Plasma Cell Dyscrasiasmentioning
confidence: 99%
“…The incidence of IGH translocations is significantly higher in pPCL than in MM. Several studies show that t(11;14) leading to CCND1 dysregulation are significantly more frequent in pPCL than in MM, reaching percentages as high as 45-70% in some series [8,17,18,[21][22][23][24]27,40,41]; also noteworthy is the high proportion of t(14;16) detected in pPCL compared with MM (13-25% vs. 1-5%, respectively), which is supported by five studies [18,21,23,36,41]. Conversely, in most of the studies, t(4;14) has been found to be less frequent in pPCL than in MM [23,36,38].…”
Section: Cytogenetic Abnormalitiesmentioning
confidence: 99%
“…MYC rearrangements have also been found in PCL, although the reported incidence varies between 13% and 40% [8,40,48]. Moreover, an association between MYC rearrangement and shorter overall survival of pPCL patients has been shown [8].…”
Section: Cytogenetic Abnormalitiesmentioning
confidence: 99%